Developmental consequences of mutations in the 84B -tubulin gene of Drosophila melanogaster. - Matthews, K.A.; Kaufman, T.C. (Developmental Biology, 1987)
Developmental effects of six mutations in the gene encoding the majority of alpha-tubulin in all tissues at all stages of Drosophila melanogaster development have been examined. All six alleles produce at least partially stable alpha 84B protein. In genetic assays, two of these alleles approximate the null condition. The other four alleles appear to form a graded series of hypomorphs. The two most severe alleles produce a semidominant maternal-effect polyphasic lethality, plus a predominantly larval recessive zygotic lethality. Clonal analysis of one of these alleles suggests it is a cell lethal. Worsening of the lethal phenotype (negative complementation) occurs in most interallelic heterozygotes involving these two mutations. As hemizygotes, the other four alleles are predominantly larval/pupal lethals. Partial complementation is achieved by most interallelic heterozygotes involving these four alleles. Phenotypic defects associated with the six tubulin mutation include disrupted embryos, pseudopupae, pharate adults with defects in various cuticular pattern elements, pharate adults with retarded head development, adults with leg tremors and extremely short life spans, and viable but sterile adults with bristle defects.